2016
DOI: 10.1063/1.4944922
|View full text |Cite
|
Sign up to set email alerts
|

Scaling studies of H-mode pedestal characteristics on Experimental Advanced Superconducting Tokamak

Abstract: The characteristics of high-confinement mode (H-mode) pedestal are examined on the Experimental Advanced Superconducting Tokamak. It is found that they are closely dependent on each other between electron pedestal characteristics and global parameters for all types of edge localized mode (ELM). The scaling of pedestal temperature based on thermal conduction and pedestal pressure width is carried out. Based on pedestal pressure gradient and pedestal density, six pedestal pressure width models are applied to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…In this section we study the collisionless pitch angle dispersion effects on the synchrotron radiation spectra emitted by various runaway electron distribution functions. Previous studies using a full-orbit description of RE in toroidal plasmas [21,27,28] have shown that due to the variation of the magnetic field seen by runaways along their orbits, they experience collisionless pitch angle dispersion, even in the the case where collisions or synchrotron radiation losses are not included. Because the synchrotron radiation of each electron strongly depends on its pitch angle, it is expected that the resulting synchrotron emission of different ensembles of runaway electrons will show non-trivial changes with respect to the results inferred from distributions that do not take into account collisionless pitch angle dispersion effects.…”
Section: Full-orbit Effects On Synchrotron Emission Of Various Rementioning
confidence: 99%
“…In this section we study the collisionless pitch angle dispersion effects on the synchrotron radiation spectra emitted by various runaway electron distribution functions. Previous studies using a full-orbit description of RE in toroidal plasmas [21,27,28] have shown that due to the variation of the magnetic field seen by runaways along their orbits, they experience collisionless pitch angle dispersion, even in the the case where collisions or synchrotron radiation losses are not included. Because the synchrotron radiation of each electron strongly depends on its pitch angle, it is expected that the resulting synchrotron emission of different ensembles of runaway electrons will show non-trivial changes with respect to the results inferred from distributions that do not take into account collisionless pitch angle dispersion effects.…”
Section: Full-orbit Effects On Synchrotron Emission Of Various Rementioning
confidence: 99%
“…Through the preservation of geometric structures, the geometric algorithms in the particle pusher module equip APT with long-term stability. For example, it has been verified that VPAs can trace the dynamics of particle correctly for tens of billion steps [5,[9][10][11]13]. Besides the geometric algorithms, traditional algorithms, such as the Runge-Kutta algorithms of different orders, are also available in APT.…”
Section: Architecture Of Aptmentioning
confidence: 99%
“…The synchrotron radiation and the gravitation field are treated as effective field in particle pushers. Even though the geometric structure of Lorentz system is modified, the geometric algorithms can still guarantee secular stability due to the preservation of electromagnetic geometric structure [11,13]. To calculate random forces, such as collisional force and bremsstrahlung force, APT also provides numerical stochastic differential equations pushers to give exquisite random simulation.…”
Section: Architecture Of Aptmentioning
confidence: 99%
See 2 more Smart Citations